2020
DOI: 10.1007/s00170-020-05927-1
|View full text |Cite
|
Sign up to set email alerts
|

An efficient generation grinding method for spur face gear along contact trace using disk CBN wheel

Abstract: In order to further improve the grinding efficiency of face gear, this paper presents a novel method for grinding face gear along contact trace using disk CBN wheel. Firstly, the grinding principle of face gear is studied, and the tooth surface equations of rack and gear shaper cutter are derived, thus formulating the tooth surface equation of disk CBN wheel. Secondly, considering the structure of the face gear grinding machine tool and the impact of the grinding wheel parameters on the face gear tooth surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…31 Here, the variable transmission ratio pinion designed using the gear element method is manufactured via CNC end milling on universal multi-axis milling machines, and the prototype is shown in Figure 19. Hobbing 32,33 and grinding 34,35 are high-efficiency gear production process, while the corresponding CNC machines and tools are complex and specialized. Thus, further investigation is required.
Figure 19.Prototype of the variable transmission ratio pinion.
…”
Section: Manufacture Of Variable Transmission Ratio Pinion Prototypementioning
confidence: 99%
“…31 Here, the variable transmission ratio pinion designed using the gear element method is manufactured via CNC end milling on universal multi-axis milling machines, and the prototype is shown in Figure 19. Hobbing 32,33 and grinding 34,35 are high-efficiency gear production process, while the corresponding CNC machines and tools are complex and specialized. Thus, further investigation is required.
Figure 19.Prototype of the variable transmission ratio pinion.
…”
Section: Manufacture Of Variable Transmission Ratio Pinion Prototypementioning
confidence: 99%
“…Experiments have verified that the face gears ground by this method can obtain higher precision. Chu [16] et al proposed a method of grinding face gears along the contact trajectory using a disk-shaped CBN grinding wheel, and carried out the grinding experiment of the face gears on a five-axis grinding machine. Ming et al [2] established a finite element model grinding face gear for the temperature field with the disc grinding wheel.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a prototype with complex geometries can be fabricated easily [ 16 ]. Chu et al [ 17 ] proposed an efficient generation grinding method for a spur face gear along the contact trace using a disk CBN wheel. Results demonstrated that the proposed method breaks new ground for the engineering application of face gears.…”
Section: Introductionmentioning
confidence: 99%